PENGARUH LOKASI DAN PROMOSI TERHADAP MINAT BELI KONSUMEN RESTORAN AYAM SAMBAL COBEK DI SUKAMAJU SEI MENCIRIM - Dewi Sundari Tanjung; Yurmaini Yurmaini; Yusrina Aulia Lubis (HIBRUL ULAMA, 2025)
This research aims to determine whether location and promotion affect consumer purchase interest of Ayam Sambal Cobek Restaurant in Sukamaju Sei Mencirim. This research is a quantitative research. This study uses primary data with data collection using a questionnaire. The population in this study were all consumers who came to Ayam Penyet Cobek Restaurant. The sample size used was multivariate with the number of samples studied being 60 respondents. Data analysis used multiple linear regression. The results showed that the location variable (X1) and the promotion variable (X2) simultaneously had a significant effect on the purchase interest variable (Y). This can be seen from the significance value of the influence of the location variable (X1) and the promotion variable (X2) on the purchase interest variable (Y) 0.000 <0.05 and the calculated F of 9.467 was greater than the F table of 3.15. Based on the results of multiple linear regression analysis of variable X against Y, a regression equation can be obtained, namely Y = 21.769 + -0.315 X1 + 0.602 X2 Based on the results of the t-test analysis (Partial) t count of the effect of the promotion variable (X2) on the purchase interest variable (Y), the regression coefficient is 0.602 and the t count is 3.904 with a significance of 0.000. So it can be concluded that the promotion variable (X2) has a positive and significant effect on the purchase interest variable (Y) of Consumers at the Ayam Sambal Cobek Restaurant in Sukamaju Sei Mencirim.